Лексические средства семантики невыразимого в современном газетном дискурсе - Nemich, Natalʹja (Acta Universitatis Lodziensis. Folia linguistica rossica, 2020)
The article studies the lexical means of the semantics of the inexpressible. The inexpressible is a functional and semantic category of the Russian language which serves to convey the impossibility of expressing an object of speech by speech participants. The dynamic development of the printed media has a huge impact on the production and distribution of newspaper texts. The relevance of our research lies in the fact that newspaper texts are contemporarily one of the most common forms of language existence. The modern newspaper discourse has been dominated by the evaluative and influencing orientation. Today we can talk about a special pragmatic intensity of newspaper texts and their saturation. One of the semantic components of intensity is the semantics of the inexpressible. The purpose of the article is to identify the existence of unspeakable semantics in modern newspaper texts. Taking into account the rich potential of newspaper discourse as a sphere that produces all new methods of implementing the category of imagery, we believe that the study of the semantic and functional properties of the inexpressible is an urgent research objective. In the modern newspaper discourse, authors use the concept of ‘inexpressible’ and its lexical-semantic group as a criterion for the impossibility of expressing things in words. In newspaper texts, the semantics of the inexpressible is expressed by a wide range of lexical means: adjectives with a prefix that conveys the semantics of negation, deprivation (inexpressible, indescribable, indescribable, unspeakable, etc.) and their derivatives, such as indescribable, unspeakable, indescribable, inexplicable, etc.; verb phrases that it is impossible to express (convey say); oxymoron as an expression of the inexpressible; phraseological units with no words (to express). The most frequent in the modern newspaper discourse, in terms of the transfer values of unspeakable, are the adjectives unspeakable, indescribable and their derivatives, mid-adverb, grammatical and lexical variants of phraseological units-sentences, such as no words, not finding words, words cannot describe and paraphrased verbs with negation, such a can’t tell, not words, I cannot say.